Hypodontia and Delayed Dentition as the Primary Manifestation of Cleidocranial Dysplasia Presenting with a Diagnostic Dilemma - Radhika Chopra; Mohita Marwaha; Payal Chaudhuri; Kalpana Bansal; Saurabh Chopra (Hindawi Limited, 2012)
Cleidocranial dysplasia is a rare autosomal disorder which manifests as partial or complete absence of clavicles, multiple supernumerary teeth, and delayed closure of fontanelle. Classical cases of cleidocranial dysplasia are easily diagnosed very early in the life. However, cases with partial manifestation of the syndrome and noncontributory family history are difficult to diagnose. Here, we report a case of 8.5-year-old girl child who presented with delayed tooth development (without any supernumerary teeth), anterior open fontanelle, and normal clavicles, thus resulting in a diagnostic dilemma.